Dasar Pertimbangan Hakim dalam Gugatan Rekonvensi (Studi Perkara Nomor: 0354/Pdt.G/2015 /PA.Tnk - Meita Djohan Oelangan (KEADILAN PROGRESIF, 2016)
Each Court Decision in civil cases should ideally be met and implemented properly by the defendant Rekonvensi, this should not be a problem if the fulfillment of obligations met by the defendant Rekonvensi (husband), permaslahan in this study is on what basis the consideration of the judges in favor of rekonvensi due to divorce divorce in case the decision No. 0345 / Pdt.G / 2015 / PA.Tnk. Juridical Normative and Empirical approach, the data type of the data is secondary and primary data. The Data collection and Library Studies Field Studies were then qualitatively Analyzed results showed that the judges also favor rekonvensi on the basis of evidence in the trial which is proven by the truth where the defendant is not in a state of nusyuz. Decision of the judges shall meet three (3) basic values, namely justice, certainty and expediency. Religious Court suggested to the judge, in order to decide the case, actually applying three (3) the value of the legal basis, namely the rule of law, justice and expediency.